91 Mapping the specialist palliative care workforce in London's Acute Hospitals – a postcode lottery?. (14th March 2023) - Gray, Anna; Bisi-Adewole, Funmi; Buxton, Katherine; Nolan, Catherina; Sleeman, Katherine; Caroline Stirling, L
Abstract : Introduction: An estimated 75% of people who die each year could benefit from receiving palliative care. Little data exists on the specialist palliative care workforce and service provision and whether this meets defined standards. Aims: To map the specialist palliative care workforce across London and identify any differences in staffing levels and out-of-hours cover, to inform workforce planning discussions across the London Palliative and End-of-Life Care Strategic Clinical Network. Method: Service evaluation of 27 specialist palliative care teams within 19 London NHS Hospital Trusts (August-December 2022). The following data were collected: numbers of whole-time-equivalent establishment and staff-in-post for clinical and non-clinical roles; hospital bed numbers, annual service referral numbers, and annual deaths (surrogate markers of service demand). Descriptive statistical analysis compared staff establishment levels per 1000 beds, referrals, and deaths. Also, data on vacancy rates and out-of-hours cover for each team were analysed. Results: All 27 teams provided data. The median ratio of medical staff to 1000 beds/referrals/deaths was 5.5, 2.5 and 3.2 respectively; the median ratio of nursing staff to 1000 beds/referrals/deaths was 14.9, 6.1 and 7.5 respectively, with wide variation across services. 48% of teams had an underfilled staffing establishment; the median vacancy rate was 10.2% (range 0.5%-42%). 44% of teams provided a 7-day face-to-face service with 24/7 telephone support. The proportion of teams with specialist social workers and psychologists in their establishment was 37% and 26% respectively. Results are subject to final verification. Conclusion: Our results demonstrate wide variation in hospital specialist palliative care workforce levels across London, and levels of out-of-hours cover. Whilst the heterogeneous nature of hospitals make comparisons challenging, our findings indicate inequity in provision. Replication of this mapping exercise across wider Strategic Clinical Networks in England is important to understand variation in workforce and service provision at a national level.